2023
DOI: 10.1038/s41467-023-38963-y
|View full text |Cite
|
Sign up to set email alerts
|

High-rate and selective conversion of CO2 from aqueous solutions to hydrocarbons

Abstract: Electrochemical carbon dioxide (CO2) conversion to hydrocarbon fuels, such as methane (CH4), offers a promising solution for the long-term and large-scale storage of renewable electricity. To enable this technology, CO2-to-CH4 conversion must achieve high selectivity and energy efficiency at high currents. Here, we report an electrochemical conversion system that features proton-bicarbonate-CO2 mass transport management coupled with an in-situ copper (Cu) activation strategy to achieve high CH4 selectivity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The p-d orbital hybridization of Cu and Ga adjusts the binding strength of *CO facilitating C–C coupling. Dinh et al reported a flow cell fabricated with porous a Cu electrode and a bipolar membrane . The Cu was activated in situ by cycling between positive and negative bias, and the bipolar membrane ensured that bicarbonates were regenerated in situ to CO 2 .…”
Section: Gaseous Products From Flow or Mea Cellsmentioning
confidence: 99%
“…The p-d orbital hybridization of Cu and Ga adjusts the binding strength of *CO facilitating C–C coupling. Dinh et al reported a flow cell fabricated with porous a Cu electrode and a bipolar membrane . The Cu was activated in situ by cycling between positive and negative bias, and the bipolar membrane ensured that bicarbonates were regenerated in situ to CO 2 .…”
Section: Gaseous Products From Flow or Mea Cellsmentioning
confidence: 99%
“…Bipolar membrane (BPM)-based electrolyzers, however, can desorb and compress CO 2 from an alkaline carbon capture solution through a pH swing process . This in situ production of CO 2 can then undergo CO 2 reduction reaction (CO 2 RR) to form products such as CO, CH 4 , C 2 H 4 , HCOO – , and C 2 H 5 OH. One critical challenge with this configuration is that excessive production of protons at the BPM junction can create a locally acidic region near the catalyst, promoting the hydrogen evolution reaction (HER) instead of CO 2 RR (lowering the C 1+ or 2+ FE). , Most prior investigations of (bi)­carbonate electrolysis with a BPM focus on the formation of C 1 products (i.e., CO, syngas, and CH 4 ). The production of pure syngas (mixture of CO and H 2 ) has also been demonstrated within a carbonate-based electrolysis cell. , However, few have demonstrated the production of C 2+ products from bicarbonate or carbonate-based electrolytic cells. ,, Controlling the local pH emerges as a crucial factor as an acidic condition is essential for CO 2 release from (bi)­carbonate, while an alkaline condition is necessary to inhibit HER and promote multicarbon product formation at the catalyst-layer–BPM interface. Additionally, the generation of CO 2 from (bi)­carbonate is highly dependent on various parameters, such as the concentrations of (bi)­carbonates, bulk pH, and applied current densities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years an increase emission of CO 2 has been recorded due to the combustion of fossil fuels and industrial processes [1,2] . Therefore, different techniques like photocatalysis, electrocatalysis and thermal catalysis have been developed for the conversion of CO 2 to useful chemical fuels, [3–7] and among them, thermal conversion of CO 2 to methane is a widely used process to obtain natural gas at mild condition [8–11] . However, CO 2 methanation is a thermodynamically favored and kinetically limited reaction, designing an active catalyst is required for this exothermic reaction.…”
Section: Introductionmentioning
confidence: 99%